Rossolimo-Melkersson-Rosenthal syndrome as a manifestation of lip sarcoidosis - Yuri N. Perlamutrov; Alexey U. Drobyshev; Kira B. Olkhovskaya; Andrey A. Miterev; Elena N. Plehanova (State Scientific Center of Dermatovenereology and Cosmetology, 2022)
A 38-year-old female patient complained of lip augmentation. With a preliminary diagnosis of RossolimoMelkerssonRosenthal syndrome (monosymptomatic form), chronic fissure of the lower lip, the patient was sent for examination in order to exclude tumor pathology and vascular malformation. According to the results of a comprehensive clinical and laboratory examination, it was found that lip enlargement is due to the formation of granulomas. Additional follow-up by a pulmonologist confirmed the presence of sarcoidosis of the lungs with involvement of the mediastinal lymph nodes. A comprehensive examination made it possible to verify the diagnosis of multisystem sarcoidosis in a patient with macrocheilitis. As a result of complex therapy using surgical methods and systemic glucocorticosteroids, a rapid dynamics of clinical symptoms was observed and remission was achieved. This clinical case demonstrates a combination of sarcoid lesions of the tissues of the mediastinal lymph nodes, lung parenchyma and lips. It was the presence of macrocheilitis that was the main reason for visiting a dermatovenereologist and was the reason for choosing the subsequent tactics of examination and treatment. As a result of complex therapy using surgical methods of treatment and systemic glucocorticosteroids, carried out entirely within the framework of the program of state guarantees of free medical care for citizens, a stable remission of the disease was achieved.